ANALISIS EFEKTIFITAS TERAPI KOMBINASI ANTIPLATELET ASPIRIN-CLOPIDOGREL DENGAN ASPIRIN-TICAGRELOR PADA PASIEN SINDROM KORONER AKUT: SYSTEMATIC LITERATURE REVIEW - Anwar, Andrian Hoerul (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Acute Coronary Syndrome (ACS) is one of the leading causes of cardiovascular morbidity and mortality, making dual antiplatelet therapy (DAPT) a crucial component of treatment. The combination of aspirin-clopidogrel has long been used, but its effectiveness is limited by genetic resistance, whereas aspirin-ticagrelor offers a faster and more consistent antiplatelet effect. This study aims to analyze the effectiveness and safety of both regimens through a Systematic Literature Review (SLR) by searching PubMed, Scopus, ScienceDirect, and Cochrane Library for articles published between 2015 and 2025. The results show that aspirin-ticagrelor is more effective in reducing Major Adverse Cardiovascular Events (MACE), including myocardial infarction, stroke, and cardiovascular mortality, but is associated with a higher risk of major bleeding and dyspnea. Conversely, aspirin-clopidogrel is considered safer and more affordable, although its effectiveness is relatively moderate. Therefore, the choice of DAPT should be individualized according to thrombotic and bleeding risks as well as patients’ economic conditions, to ensure appropriate therapy particularly in developing countries such as Indonesia.